Social connections and suicidal behaviour in young Australian adults: Evidence from a case–control study of persons aged 18–34 years in NSW, Australia - Allison Milner; Andrew Page; Stephen Morrell; Coletta Hobbs; Greg Carter; Michael Dudley; Johan Duflou; Richard Taylor (SSM: Population Health, 2015)
Purpose: There is evidence that social isolation is a risk factor for suicide, and that social connections are protective. Only a limited number of studies have attempted to correlate the number of social connections a person has in their life and suicidal behaviour. Method: Two population-based case–control studies of young adults (18–34 years) were conducted in New South Wales, Australia. Cases included both suicides (n=84) and attempts (n=101). Living controls selected from the general population were matched to cases by age-group and sex. Social connections was the main exposure variable (representing the number of connections a person had in their life). Suicide and attempts as outcomes were modelled separately and in combination using conditional logistic regression modelling. The analysis was adjusted for marital status, socio-economic status, and diagnosis of an affective or anxiety disorder. Results: Following adjustment for other variables, those who had 3–4 social connections had 74% lower odds of suicide deaths or attempts (OR=0.26, 95% CI 0.08, 0.84, p=0.025), and those with 5–6 connections had 89% lower odds of suicide deaths or attempts (OR=0.11 95% CI 0.03, 0.35, p<0.001), compared to those with 0–2 social connections. With the number of social connection types specified as a continuous variable, the odds ratio was 0.39 per connection (95% CI 0.27, 0.56, p<0.001). Conclusions: A greater number of social connections was significantly associated with reduced odds of suicide or attempt. This suggests that suicide prevention initiatives that promote increased social connections at an individual, familial, and wider social levels might be effective.